2002
DOI: 10.1063/1.1421222
|View full text |Cite
|
Sign up to set email alerts
|

Structure and properties of carbon onion layers deposited onto various substrates

Abstract: 120 keV carbon ions implantations at high fluences (0.5–8×1017 ions cm−2) were performed at elevated temperature (⩾500 °C) in silver layers deposited on various substrates (Si (100), 304 L stainless steel, and pure fused silica). Spherical carbon onions (3–15 nm in diameter) were so produced in the silver layers. A pure carbon onion thin film deposited on the substrate was obtained after annealing in vacuum. Atomic force microscopy and high-resolution transmission electron microscopy experiments were performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(30 citation statements)
references
References 38 publications
2
28
0
Order By: Relevance
“…The p/p* excitation is centred at 6.1 eV for carbon nano- onions compared to 7 eV for graphite sheets. These data are in good agreement with values observed by Cabioc'h et al [18,19] on carbon onions with a p/p* peak at 5.7 eV and a plasmon loss peak maximum at 24 eV for a momentum transfer of 0.15 A -1 (corresponding nearly to our operating conditions). These significant differences are basically attributed to the curvature of sheets, the coupling of electrons on the spherical shells being well different from the coupling in the planar case.…”
Section: Tem-eels Characterization Of Carbonsupporting
confidence: 92%
“…The p/p* excitation is centred at 6.1 eV for carbon nano- onions compared to 7 eV for graphite sheets. These data are in good agreement with values observed by Cabioc'h et al [18,19] on carbon onions with a p/p* peak at 5.7 eV and a plasmon loss peak maximum at 24 eV for a momentum transfer of 0.15 A -1 (corresponding nearly to our operating conditions). These significant differences are basically attributed to the curvature of sheets, the coupling of electrons on the spherical shells being well different from the coupling in the planar case.…”
Section: Tem-eels Characterization Of Carbonsupporting
confidence: 92%
“…Sufficient quantities could be produced for investigation of their optical, electronic and tribological properties. [14][15][16][17] These carbon onions were characterized by Fourier transform infrared ͑FTIR͒ spectroscopy 16 and it was shown that the most stable state for the onions consists of concentric spheres of fullerenes C n ͑n = 60, 240, …͒. Until now, the electronic properties of the onions were characterized only by spatially resolved EELS in transmission 15,18 and reflection mode.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies on their tribological properties have been reported so far. Cabioc'h et al [3] studied the tribological properties of silver films containing carbon onions and observed an increase in the lifetime of the coatings when carbon onions are present. Their use as solid lubricant between a steel ball and a silicon wafer lead to a lower friction coefficient and a lower wear compared to graphite [4].…”
Section: Introductionmentioning
confidence: 98%